Usage of Oral Rehydration Salts and Other Treatments in Management of Diarrhoea Among Children Under-Five Years Attending Primary Health Care Facilities in Dar es Salaam (Tanzania Medical Journal, 2020)
BackgroundDiarrhoeal disease is highly preventable and easily manageable, yet remains a significant cause of childhood mortality in Tanzania. Since dehydration caused by acute diarrhoea is the main contributor to mortality, key measures to treat diarrhoea include rehydration using oral rehydration salts (ORS) and zinc supplements. Therefore, this study aimed to assess ORS use, pediatric zinc and antibiotics in the management of diarrhoea in children under-five years attended at the primary health care facilities in Dar es salaam, Tanzania. Also, factors associated with antibiotics usage were determined.MethodsA cross-sectional study was conducted from March to September 2019. Ten dispensaries were selected from five Dar es salaam municipalities in Tanzania. A total of 301 children under-five years with diarrhoea were enrolled. Information on socio-demographic characteristics was obtained by asking the parents/guardians, whereas clinical characteristics, laboratory results, diagnosis, and treatment were extracted from children’s files. The information obtained was recorded in the structured questionnaire. Data were analyzed using statistical package for social science software, version 22.0. Descriptive statistics were used to summarize the information collected. The multivariable logistic regression was used to determine factors associated with antibiotics use in diarrhoea management, whereby p<0.05 was considered statistically significant.ResultsOf 301 children enrolled, 85.7% had acute watery diarrhoea. ORS and pediatric zinc were prescribed to 75.1% and 48.8% of children, respectively. At least one antibiotic was prescribed to more than half (66.8%) of the enrolled children. The odds that antibiotics were prescribed in the management of children with acute watery diarrhoea was less compared to those with bloody or persistent diarrhoea (AOR 0.1 (95% CI 0.02 – 0.3) p< 0.01). Also, children attending health facilities in Ilala municipality had 2.1 (AOR (95%CI 1.2 – 3.8) p = 0.014) times odds of being given antibiotics compared to those attended at other health facilities in other municipalities.ConclusionORS usage in managing diarrhoea among children under-five years is higher than the use of pediatric zinc. A high incidence of antibiotics use in acute watery diarrhoea management was observed, which is against recommended guidelines. The study recommends continuing education to health care providers and the community on proper management of diarrhoea in children under-five years.Keywords: Diarrhoea; children under-five, pediatric zinc and oral dehydration salts.